RAPD profile for four mithuD populations - BHUSAN, S; SHARMA, DEEPAK; RAJKHOWA, C; BUJARBARUAH, K M (The Indian Journal of Animal Sciences, 2011)
Primers (19) were screened against 4 strains of mithun and out ofthese primers 17 primers detected polymorphism between these strains. Out of 199 loci scored, 74 (37.18%) ""ere polymorphic. The bands resolved in the size range from 270 to 2750 bp. The primers differed not only in number of bands amplified but also for their size range. The average number ofbands per primer ranged from 8.1 to 9.3 in different strains. Â